Ushul al-Ikhtilaf dalam Masalah Ijtihadiyah: Telaah Kritis atas Pemikiran Ibnu Taimiyah : Ushul al-Ikhtilaf in the Problem of Ijtihadiyah: A Critical Study of Ibn Taimiyah's Thoughts - Muhammad Ikhsan; Azwar, Azwar (DIRASAH: Jurnal Kajian Islam, 2025)
Ibn Taymiyyah is widely recognized as one of the key figures in the renewal (tajdid) of Islamic thought. Despite the controversies surrounding his views, his contributions to the formulation of principles governing differences of opinion (Ushul al-Ikhtilaf) remain significant. This study aims to examine Ibn Taymiyyah’s concept of Ushul al-Ikhtilaf. It employs a qualitative approach using interpretative-hermeneutic analysis of documentary data. The findings reveal that Ibn Taymiyyah viewed differences in ijtihadi matters as a natural aspect of Islamic legal dynamics, provided they are based on valid Shariah grounds. He emphasized several key principles: no condemnation should occur without clear evidence, coercion in matters of differing opinions is not allowed, judgment and social ostracism must be avoided, and mujtahids who err in their ijtihad deserve excuse and reward if their efforts are sincere and based on valid interpretation. Even in error, a mujtahid should not be declared disbeliever or sinner. Nonetheless, granting such excuse does not negate the obligation to explain the truth in a scholarly and balanced manner for the sake of preserving the purity of the religion and the public good. Thus, Ibn Taymiyyah’s perspective on Ushul al-Ikhtilaf promotes a scholarly, tolerant, and just approach in addressing differences among Muslims.